Investigation of Leakage Current Behavior Based on Current Symmetry Due to Multiple Positive and Negative Impulses - Chaitawat Chuayin; Norasage Pattanadech; Matthieu Zinck; Suthat Suksagoolpanya; N. Sontayananon; Chanin Bunlaksananusorn (My University, 2024)
The failure of Metal Oxide Surge Arrester becomes a major issue of the utilities. A strategy which is commonly utilized to diagnosis the problems is leakage current measurement in any terms of current e.g., total leakage current, resistive leakage current, capacitive leakage current. This paper aims to study the symmetrical behavior of the leakage current caused by positive and negative multiple lightning currents. The asymmetrical leakage currents were observed with 24 kV, 10kA commercial surge arrester which divided in to 2 groups. The experiment was conducted by measuring the leakage current at rated voltage and 1-mA reference voltage before applying a prepare of 5 shots of 10-kA positive and negative standard impulse current (8/20 μs) to groups I and II individually. After that, more 5 shots were applied to the specimens once more. The resistive leakage current at rated voltage and 1-mA reference voltage measurement were then performed after each impulse current application. Hence, groups I and II were applied with 15-shots multiple negative and positive impulse current respectively. The resistive leakage current at rated voltage and 1-mA reference voltage were performed after each 5 shots of impulse current. The experiment results show that (1) applying multiple impulse currents will make the asymmetrical leakage current. (2) positive polarity multiple impulse current creates asymmetry more than negative polarity. (3) negative polarity will increase the positive peak of leakage current and vice versa for positive polarity.
Keywords: Electrical Fault Detection and Protection; Machine Fault Diagnosis Techniques